Peningkatan Motivasi Belajar dan Kemampuan Menulis Puisi dengan Media Audio Visual pada Siswa SMK - Raisa Tiara Emeralda; Edy Suryanto; Ani Rakhmawati (TRANSFORMATIKA, 2019)
Writing poetry learning is a productive learning activity. Based on the results of interviewing teachers, there are problems in writing poetry learning at Vocational High School 1 Sukoharjo, which is difficult for the students to determine the themes, the use of diction and the less different metaphors, and the mismatch of the message with the contents of the poem. Besides, the students' motivation in following the lesson is still low. This study aims to improve learning motivation and writing skills with audiovisual media. This research is class action research that is held two-cycle. Each cycle consists of action planning, action implementation, observation, and reflection. Data research sources are through learning activity, informan, and documents. The data collection techniques used are observation, interview, and test. The validity of data was investigated through triangulation techniques of data sources and methods. The data analysis technique used in this research are comparative descriptive techniques and critical analysis technique. The results showed that the use of audiovisual media could increase learning motivation by 5.71% in pre-action, 61,76% in the first cycle, and 97,14% in the second cycle. The use of audiovisual media can also improve students' poetry writing skills by 17% in pre-action, 66% in the first cycle, and 91% in the second cycle.